Parenting When Apart: Tips for Non-Resident Fathers - Keith Gouin; Suzanna Smith; Garret D. Evans; Daniel F. Perkins (EDIS)
Revised! FCS2139, a 3-page fact sheet by Keith Gouin, Suzanna Smith, Garret D. Evans, and Daniel F. Perkins, will assist non-resident fathers in being fully and positively involved in their children's lives. Ten tips on fathering when apart give concrete, everyday ideas and suggestions for keeping these relationships strong. Revised to reflect new attitudes and beliefs regarding the roles of nonresident fathers. Published by the UF Department of Family, Youth and Community Sciences, February 2007.